Radiotherapy alone and with concurrent chemotherapy for nasopharyngeal carcinoma: A retrospective study. Issue 18 (May 2018) - Katano, Atsuto; Takahashi, Wataru; Yamashita, Hideomi; Yamamoto, Kentaro; Ando, Mizuo; Yoshida, Masafumi; Saito, Yuki; Abe, Osamu; Nakagawa, Keiichi
Abstract : Abstract: We sought to evaluate clinical outcomes and toxicities of radiation therapy (RT) alone compared to RT with concurrent chemotherapy (CCT) for nasopharyngeal carcinoma (NPC) treatment. We conducted a retrospective review of consecutive patients with biopsy-proven nonmetastatic NPC who underwent RT at our institution. From May 2001 to April 2015; 62 newly diagnosed NPC patients were treated with three-dimensional conformal radiotherapy (3D-CRT) or intensity-modulated radiotherapy (IMRT) with or without CCT. The patients were classified as follows: 8% stage I, 15% stage II, 32% stage III, and 45% stage IVA/IVB. A total of 76% of tumors were World Health Organization types II or III. Acute and late toxicities were graded according to the Common Terminology Criteria for Adverse Events version 3.0. Overall survival (OS), progression-free survival (PFS), locoregional progression-free survival (LRPFS), and distant metastasis-free survival (DMFS) were analyzed. The median follow-up period for living patients was 53 months. The median actual delivered dose was 70 Gy with a range of 28 to 70 Gy in fraction sizes of 2 Gy. The estimated 5-year OS, PFS, LRPFS, and DMFS rates were 72.7%, 59.8%, 77.9%, and 84.2%, respectively. The use of CCT was a predictive factor of significantly better OS and PFS, whereas stage IV was a significant predictor of poor OS and PFS. The most severe acute toxicities included Grade 3 mucositis in 56% and Grade 3 dermatitis in 8%. Subset analysis revealed that Grade 2 xerostomia was significantly lower in the IMRT (23%) group than in the 3D-CRT (52%) group ( P = .02). RT yielded favorable outcomes. CCT was associated with longer PFS and OS than RT alone. Abstract : Supplemental Digital Content is available in the text